Can Land Transfer Alleviate Multidimensional Relative Poverty in Rural Areas? - Benjian Wu; Yiyuan Rong; Xinyu Liang; Haibo Zhu; Xue Shi (Land)
After eliminating absolute poverty, China’s anti-poverty efforts have shifted towards multidimensional relative poverty. This study uses microdata from the Chinese Academy of Agricultural Sciences (CAAS) from 2012 to 2021, applies the Kakwani index to construct a multidimensional relative poverty indicator, and uses an endogenous transformation model to analyze the impact of land transfer on multidimensional relative poverty in rural areas. The study found that (1) land transfer can effectively reduce the multidimensional relative poverty of farm households. (2) Land transfer has a better mitigating effect on young farmers, farmers with higher literacy levels, and farmers who have not acute poverty. (3) Land transfer alleviates multidimensional relative poverty by increasing agricultural mechanization, business income, off-farm employment, and wage income. (4) The effects of land transfer out and land transfer in on the dimensions of multidimensional relative poverty are heterogeneous.